Girder Stiffness Distribution for Unbraced Columns - Stockwell, Jr. (Engineering Journal, 1976)
In the gravity design of unbraced columns, the Alignment Chart (Fig. C1.8.2) in the AISC Commentary is very useful. However, this chart is conservative due to several assumptions made in its preparation. One of these assumptions is that the column above and the column below a particular joint share equally in the girder stiffness available at that joint. In reality this is rarely how it works. What happens is that each column takes stiffness in proportion to its particular need for restraint.* This paper discusses a rational method for distributing girder stiffness to each column tier at a given joint, and the significance of this distribution in actual design.